2006
DOI: 10.1021/jo061682x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Both the Electrophilic Center and Substituents on the Nonleaving Group in Pyridinolysis of O-4-Nitrophenyl Benzoate and Thionobenzoates

Abstract: A kinetic study is reported for reactions of 4-nitrophenyl benzoate (1c) and O-4-nitrophenyl X-substituted thionobenzoates (2a-e) with a series of pyridines in 80 mol % H2O/20 mol % dimethyl sulfoxide (DMSO) at 25.0 +/- 0.1 degrees C. O-4-Nitrophenyl thionobenzoate (2c) is more reactive than its oxygen analogue 1c toward all the pyridines studied. The Brønsted-type plot is linear with beta(nuc)=1.06 for reactions of 1c but curved for the corresponding reactions of 2c with beta(nu)c decreasing from 1.38 to 0.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…However, the k 2 /k -1 ratios for the reactions of substrates 1a-c are almost identical for a given pyridine. This is consistent with our previous report that the electronic nature of the substituent X in the nonleaving group does not influence the k2/k-1 ratio for pyridinolysis of O-4-dinitrophenyl X-substituted thionobenzoates 3 and aminolysis of 2,4-dinitrophenyl X-substituted benzenesulfonates. 7a The effect of pyridine basicity on k1 is illustrated in Figure 3.…”
Section: 7asupporting
confidence: 93%
See 3 more Smart Citations
“…However, the k 2 /k -1 ratios for the reactions of substrates 1a-c are almost identical for a given pyridine. This is consistent with our previous report that the electronic nature of the substituent X in the nonleaving group does not influence the k2/k-1 ratio for pyridinolysis of O-4-dinitrophenyl X-substituted thionobenzoates 3 and aminolysis of 2,4-dinitrophenyl X-substituted benzenesulfonates. 7a The effect of pyridine basicity on k1 is illustrated in Figure 3.…”
Section: 7asupporting
confidence: 93%
“…In contrast, we have shown that pKa o and k2/k-1 ratio are not influenced by the electronic nature of substituent X in the nonleaving group for pyridinolysis of O-4-nitrophenyl X-substituted thionobenzoates 3 and aminolysis of 2,4-dinitrophenyl X-substituted benzenesulfonates in 80 mol % H2O/20 mol % DMSO. 7a It has been found that the Hammett plots for these reactions are not linear, e.g., the ρ value decreases as the substituent changes from EDGs to EWGs.…”
Section: Scheme 1 Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…The curvature centre (pK a 0 ) of the curved Brønsted-type plots occurred at pK a = 9.3 regardless of the electronic nature of the substituent X in the non-leaving group. 48 Boron trifluoride and indium(III) triflate were found to catalyse efficiently the isomerization of thionolactones (26) to thiolactones (27) in good yields. When applied to an optically active γ -thionolactone [(R)-28], the isomerization reaction proceeded with complete inversion of configuration to [(S)-29] by using BF 3 .OEt 2 (Scheme 9).…”
Section: Pathmentioning
confidence: 99%